The Role of Self-Efficacy as a Mediator in Determining the Factors Influencing Entrepreneurial Intention - Fitri Apriliani; Agus Wahyudin; Sandy Arief (Universitas Negeri Semarang, 2025)
This study has the objective to test the connection among entrepreneurial knowledge, family environment, subjective norms, and entrepreneurial motivation through self-efficacy. The population in this study were 1,227 students of the Faculty of Economics and Business, Semarang State University, class of 2020. The sample size was determined utilizing the Slovin formula, outcomeing in 155 respondents. The sampling technique used was proportionate random sampling. Data collection was conducted utilizing a questionnaire that had been validated for validity and reliability. Data analysis techniques included descriptive analysis, inferential analysis, and the Sobel test. The outcomes of the study reveal that (1) entrepreneurial knowledge, family environment, subjective norms, entrepreneurial motivation, and self-efficacy have a positive and significant influence on entrepreneurial intention; (2) entrepreneurial knowledge, family environment, subjective norms, and entrepreneurial motivation have a positive and significant influence on self-efficacy; (3) self-efficacy mediates the influence of entrepreneurial knowledge, family environment, subjective norms, and entrepreneurial motivation on entrepreneurial intention. This study is expected to contribute to the development of knowledge and test the Theory of Planned Behavior and Social Cognitive Theory related to entrepreneurial intention among university students